(untitled) (Global Journal of Computer Science and Technology, 2022)
Abstract In the current era cybersecurity problems are one of the critical problems that threaten the organizations assets since they may cause a big financial and moral loss and in the parallel the with the advent of the Machine Learning and Artificial Intelligence techniques It is important and wise to use these technologies to help in achieving cybersecurity for organizations assets due to accurate work of these systems and saving time effort and cost So this research develops a model that uses machine learning technology to detect the vulnerability in the information security of the organizations assets to avoid as possible the lack of the information security in organizations assets and thus avoid the financial and moral loss that such organizations may face